Olive pits as a high-resolution proxy archive of climate: Δ13C in modern and archaeological olive pits reflecting environmental conditions. (15th October 2022) - Ehrlich, Yael; Raj, Harsh; Mintz, Eugenia; Regev, Lior; Boaretto, Elisabetta
Abstract: Charred olive pits are frequently preserved in archaeological sites in Israel, from ca. 5000 BCE. As olive fruits grow during one season, the carbon comprising their pits reflects their year of growth, making charred olive pits found in situ ideal for radiocarbon dating of archaeological contexts. An additional aspect, up until now not explored, is utilizing the ratio between the stable carbon isotopes (δ13C) in these charred olive pits as a proxy for climate. Olive pits provide multiple advantages as a proxy, allowing for higher resolution of climate reconstruction, both spatially and temporally, reflecting the environment in which the olive trees were growing, and humans were living. Here we show firstly, an analysis of modern olive pits and assess the connection between pit cellulose δ13C and aridity index. Specifically, we identify the threshold Δ13C for olive trees under severe drought stress as below 15.5 ± 0.5‰. Next, as olive pits are usually found charred in archaeological contexts, we evaluated the effect of charring on the δ13C signal of the modern olive pits. Finally, we present Δ13C values of more than 500 charred olive pits from 51 archaeological sites in Israel, spanning ∼6000 years. Based on these values we have identified periods of arid conditions and wet conditions in the past. Highlights: High resolution climate reconstruction in southern Levant based on charred olive pits. First time carbon isotopes in olive pits are shown to be related to climate conditions. Multiple site records allowed spatial scale-down of southern Levant past climate. Absolute 14 C dated single olive pits provide a 6000 years long climate reconstruction.